Learning Using Animated Video Media to Improve Student Learning Outcomes - Purwanti, Pio; Darusman, Yus; Zahrah, Riza Fatimah (Universitas Sebelas Maret, 2021)
This research is based on the problems that occurred at SDN Margaluyu. Through observations that have been made at SDN Margaluyu that the learning process is less attractive without the use of media. The scores of students in social studies subjects are still much below the KKM with KKM IPS scores of 75. In connection with these problems, the researchers conducted research with the aim of improving learning outcomes in social studies using animated video media. The population of this study was grade IV students, amounting to 26 students. The sampling technique used was random sampling of 10 students. The method used is classroom action research. The data collection technique used multiple choice test sheets. Obtained from the results of the analysis in cycle I, the number of students who met the KKM was 6 students or 60%, while the results of the analysis in cycle II had an increase in all students completing the KKM or 100%. So it can be concluded that learning using animated video media can improve student learning outcomes in social studies subjects on economic activity material in class IV SDN Margaluyu.